CHATODOLUMINESCENCE MICROSCOPIC ANALYSIS TO INTERPRET THE REDOX CONDITION DURING THE FORMATION OF CARBONATE VEIN - I Wayan Warmada; Retno Hartati (Geological Engineering Department Universitas Gadjah Mada, 2015)
Cathodoluminescence (CL) is generated by an electron gun coupled to an optical microscope. There are two types of chatodoluminescence, i.e., cold CL and hot CL. In the cold cathode microscopic equipment, the electrons are generated by an electric discharge between two electrodes under a low gas pressure, whereas in the hot CL microscope, the electrons are generated by heating a filament (2000–3000°C). In this paper we utilize cold CL combine with electron microprobe analysis (EMPA). The CL microscopy of carbonate shows at least three carbonate generations, i.e., rhodochrosite with dull or no luminescence, Mg-rich calcite with dark red luminescence, manganese-bearing calcite with up to 0.04 wt.% Mn with bright orange luminescence, and pure calcite and Mn-rich calcite (> 0.15 wt.% Mn) with dull or no luminescence. The result also suggests that the luminescence pattern of calcite is controlled by the amount of Mn2+. Sectoral zoning and chevron-shape growth zoning exist in some coarse-grained calcite aggregates. The sectorial zoning of calcite as reflected by dull to bright CL color indicated that slightly to more reducing environment during calcite deposition. Keywords: Chatodoluminescence, rhodochrosite, calcite, sectorial zoning